2006
DOI: 10.1590/s0036-46652006000600005
|View full text |Cite
|
Sign up to set email alerts
|

Sharing of antigens between Plasmodium falciparum and Anopheles albimanus

Abstract: SUMMARYThe presence of common antigens between Plasmodium falciparum and Anopheles albimanus was demonstrated. Different groups of rabbits were immunized with: crude extract from female An. albimanus (EAaF), red blood cells infected with Plasmodium falciparum (EPfs), and the SPf66 synthetic malaria vaccine. The rabbit´s polyclonal antibodies were evaluated by ELISA, Multiple Antigen Blot Assay (MABA), and immunoblotting. All extracts were immunogenic in rabbits according to these three techniques, when they we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…A first hypothesis is a cross-reaction with a protein within the mosquito itself [12]. It has indeed been shown that the sera of rabbits immunized with the SPf66 malaria vaccine (containing the NANP-repeat of the CSP protein of P. falciparum ) recognized several unidentified proteins of Anopheles albimanus [34]. However, if a constitutively expressed mosquito protein would be responsible for the reported false positivity, it would be observed systematically in a certain species, a higher number of false positives would be expected, and it would not explain the seasonal variation of the false positivity observed in South-Africa [12].…”
Section: Discussionmentioning
confidence: 99%
“…A first hypothesis is a cross-reaction with a protein within the mosquito itself [12]. It has indeed been shown that the sera of rabbits immunized with the SPf66 malaria vaccine (containing the NANP-repeat of the CSP protein of P. falciparum ) recognized several unidentified proteins of Anopheles albimanus [34]. However, if a constitutively expressed mosquito protein would be responsible for the reported false positivity, it would be observed systematically in a certain species, a higher number of false positives would be expected, and it would not explain the seasonal variation of the false positivity observed in South-Africa [12].…”
Section: Discussionmentioning
confidence: 99%